Effect of Cu doping on the catalytic activity of Fe3O4 in water-gas shift reactions. (9th February 2015) - Fu, Zhaoming; Wang, Jinqi; Zhang, Na; An, Yipeng; Yang, Zongxian
Abstract: The effects of the addition of Cu to a Fe3 O4 catalyst on water-gas shift reactions (WGS) are investigated using first-principle calculations. To elucidate the doping effect, the adsorption of CO and H2 O (the reactants in WGS) molecules is studied on the surfaces of pure Fe3 O4 and Cu doped Fe3 O4 . The results reveal that Cu dopants in the Fe3 O4 (1 1 1) surface are effective in enhancing the adsorption strength of CO molecules as well as in inhibiting excess water molecules from covering active sites. Simultaneously, it is found that Cu dopants improve the activity of the Fe ions adjacent to dopants for adsorbing both CO and H2 O. Therefore, it is possible to control the adsorbance of CO and H2 O to reach a proper proportion for WGS through changing the concentration of Cu promoters in the catalysts. The mechanism of doping effects is discussed based on the chemical bond theory and Bader charge analysis. Additionally, the co adsorption of CO and H2 O is studied on pure and Cu doped Fe3 O4 (1 1 1) surfaces. The calculated results also suggest that doping of Cu atoms in Fe3 O4 would improve the stability of the reactants co adsorbed on catalysts, which is beneficial for the WGS reaction. Graphical abstract: Highlights: Doping Cu in Fe3 O4 catalyst can control the adsorbed reactant ratios in WGS reaction. Doping Cu in Fe3 O4 can improve the activity of Fe ions for adsorbing CO and H2 O. Doping Cu in Fe3 O4 can enhance the co adsorption of CO and H2 O in WGS reaction.